2013
DOI: 10.1007/s12070-013-0671-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Knowledge of Harmful Effects and Exposure to Recreational Music in College Students of Delhi: A Cross Sectional Exploratory Study

Abstract: Exposure to loud sounds results in a mild to profound degree of temporary or permanent hearing loss. Though occupational noise exposure remains the most commonly identified cause of noise-induced hearing loss, potentially hazardous noise can be encountered during recreational activities. Unfortunately not much attention is being given to the increasing trend of prolonged exposure to noisy environment, in the younger generation of Indians. The purpose of our study was to know the knowledge of college students a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
16
1
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 20 publications
2
16
1
7
Order By: Relevance
“…20 The general willingness for young adults to use earplugs in music venues is low. [21][22][23] A study in the United States found that less than 10% of college students reported using hearing protection for rock concerts, discos, and sporting events. 18 Perceived individual susceptibility to hearing damage and perception of risk is likely to be one factor influencing earplug use.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…20 The general willingness for young adults to use earplugs in music venues is low. [21][22][23] A study in the United States found that less than 10% of college students reported using hearing protection for rock concerts, discos, and sporting events. 18 Perceived individual susceptibility to hearing damage and perception of risk is likely to be one factor influencing earplug use.…”
mentioning
confidence: 99%
“…Furthermore, in a study in India, less than 3% of students reported using ear protection in loud venues, despite 83% acknowledging that loud sound can have a harmful effect on hearing. 22 When exploring adolescents' perceptions of loud music and hearing protection, Vogel et al found that most adolescents often played their MP3 players at maximum volume, and although they were aware of the risks of exposure to loud music, most considered their personal vulnerability to be low. 25 A lack of awareness about the need to protect their ears from noise damage and their low levels of perceived susceptibility mean that many young people are not considering earplugs or lower volume levels as an option.…”
mentioning
confidence: 99%
“…15,16 However, the general willingness to use earplugs in music venues by attendees is low. [17][18][19] This reluctance is partly owing to the lack of evidence and general knowledge on the effectiveness of earplugs in protecting hearing and the scarce availability of earplugs. 15 A recent systematic review 20 by our research group found only 1 randomized clinical trial (RCT) on the efficacy of earplugs in concert attendees.…”
mentioning
confidence: 99%
“…Eva Almaraz-Arriaga, L en T Soc, (1) Víctor Manuel Páez-Zayas, M Gastr, (1) Liz Nicole Toapanta-Yanchapaxi, M Gastr y Hepat, (1) Alejandra Rosales-Fernández, MC, (1) Ignacio García-Juárez, M Gastr y Hepat. (1) drinter77@gmail.com (1)…”
Section: Característicasunclassified
“…Educativa, (1) Miguel Barboza-Palomino, Psic. (1) mbarbozapalomino@outlook.com.pe (1) un año en inactividad laboral. En 31% (n=12), el proveedor económico fue el paciente, y el cónyuge en 41%…”
unclassified